1968
DOI: 10.1083/jcb.38.2.403
|View full text |Cite
|
Sign up to set email alerts
|

FINE STRUCTURE OF CELL DIVISION IN CHLAMYDOMONAS REINHARDI

Abstract: Cell division in log-phase cultures of the unicellular, biflagellate alga, Chlamydomonas reinhardi, has been studied with the electron microscope. The two basal bodies of the cell replicate prior to cytokinesis; stages in basal body formation are presented. At the time of cell division, the original basal bodies detach from the flagella, and the four basal bodies appear to be involved in the orientation of the plane of the cleavage furrow. Four sets of microtubules participate in cell division. Spindle microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
243
0
1

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(258 citation statements)
references
References 44 publications
14
243
0
1
Order By: Relevance
“…Previous reports have suggested that basal bodies in C. reinhardtii dissociate from attached flagella at the onset of mitosis (Johnson and Porter, 1968;Gould, 1975). Subsequent reports, however, have suggested that flagellar resorption is completed before mitosis (Cavalier-Smith, 1974;Gaffal, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have suggested that basal bodies in C. reinhardtii dissociate from attached flagella at the onset of mitosis (Johnson and Porter, 1968;Gould, 1975). Subsequent reports, however, have suggested that flagellar resorption is completed before mitosis (Cavalier-Smith, 1974;Gaffal, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ultrastructural defect in TZs in uni2 mutant cells, the mitotic migration of the Uni2 protein to the spindle poles suggests it is not a TZ component. Previous ultrastructural studies have shown that TZs remain associated with remnants of flagella during mitosis (Johnson and Porter, 1968) and that the TZ is resorbed along with the flagellum during mitosis (Cavalier-Smith, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the mitotic cleavage furrow of C. reinhardtii contains microtubules but apparently no microfilaments (9), in contrast to most furrowing cells where microfilaments abound (14,21,23). It would appear, therefore, that C. reinhardtii restricts its ability to generate microfilaments to a brief but critical stage in its life cycle, and this ability is apparently dependent on the presence of a normal doublet zone.…”
Section: Microfilament Involvement In the Mating Regionmentioning
confidence: 99%
“…The genetics of this organism have been well studied (15) and mutants may be characterized by recombination analysis in mating cells or by complementation analysis in temporary dikaryons (26) and stable diploids (4,5). The structure of the organism's two flagella have also been well described (9,23) as have the microtubular systems which are present during interphase, mitosis, and cytokinesis (12). Flagella may be experimentally amputated and their subsequent regeneration used to study morphogenesis (19).…”
mentioning
confidence: 99%